(untitled) (Ius Novum, 2024)
The article discusses the issue of the so-called forced marriages, the criminalisation of which was introduced into the Polish criminal legislation by Act of 13 January 2023 amending Act: Code of Civil Procedure and some other acts. Introducing the provisions of Article 191b to Criminal Code is to fulfil the obligation arising from Article 37 of the Council of Europe Convention on preventing and combating violence against women and domestic violence of 11 May 2011 (Journal of Laws of 2015, item 961). In the article, in addition to the characteristics of the statutory features of new types of crimes, reference is made, inter alia, to the issue of criminal liability, concurrence of regulations and the problem of the so-called cultural defence.